2017
DOI: 10.1038/s41598-017-03783-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel complex of HAT protein TIP60 and nuclear receptor PXR promotes cell migration and adhesion

Abstract: PXR is a member of nuclear receptor superfamily and a well-characterized mediator of xenobiotic metabolism. The classical mode of PXR activation involves its binding to appropriate ligand and subsequent heterodimerization with its partner RXR. However, various factors such as post-translational modifications and crosstalk with different cellular factors may also regulate the functional dynamics and behavior of PXR. In the present study, we have identified that TIP60, an essential lysine acetyltransferase prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…It is unclear exactly how the endogenous AFT complex manifests. Several publications report the use of fluorescently tagged AFT complex components [48][49][50][51], but Tip60 in these studies shows a markedly different distribution to those reports using smaller tags, or untagged Tip60 [52][53][54]. Further differences may arise from the use of non-neuronal [51,52] or neuronal-like [53] cell lines.…”
Section: App and Tdp-43 Have Distinct Intracellular Locations In Cultmentioning
confidence: 95%
“…It is unclear exactly how the endogenous AFT complex manifests. Several publications report the use of fluorescently tagged AFT complex components [48][49][50][51], but Tip60 in these studies shows a markedly different distribution to those reports using smaller tags, or untagged Tip60 [52][53][54]. Further differences may arise from the use of non-neuronal [51,52] or neuronal-like [53] cell lines.…”
Section: App and Tdp-43 Have Distinct Intracellular Locations In Cultmentioning
confidence: 95%
“…In a previous study using PXR-overexpressing human hepatocellular carcinoma HepG2 cells, it was proposed that PXR activation induces morphological change and migration of the cells 33 . Another study using HepG2 cells also indicated that PXR promotes the migration of these cells 37 . Noteworthy, wound healing effect of indirubin was observed at 100 nM but not at higher (10,000 nM) concentration.…”
Section: Discussionmentioning
confidence: 96%
“…In another study, Bakshi et al revealed that PXR is also acetylated on Lys-170 by KAT5, a well-known KAT protein (also called TIP60), that is involved in regulating chromatin remodeling, transcription, and other nuclear processes by acetylating histone and nonhistone proteins. In this study, it was revealed that KAT5 utilizes its NR-box to interact with the LBD region of PXR and acetylates PXR at Lys-170 to induce its intra-nuclear reorganization [88]. Interestingly, these authors observed that PXR interaction with TIP60 augments the catalytic activity of TIP60 towards the acetylation of histone proteins.…”
Section: Acetylationmentioning
confidence: 88%